INTERNALISASI FALSAFAH NENGAH NYAPPUR PADA MUDA-MUDI LAMPUNG SAIBATIN SEBAGAI NILAI-NILAI PENDIDIKAN ISLAM - Sarkoni, Muhammad; Rahmat, Rahmat (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
It contains four elements: Nemui Nyimah, Sakai Sambayan, Nengah Nyappur and Beujuluk Beadek. Social problems occur in young people who commit unnatural acts such as drunkenness, free sex and the sale of drugs. If observed in depth the above-mentioned acts violate the norms of both customary norms and religious norms that are the values of Islamic education. This research is a type of qualitative investigation using a case study approach. The results of this study show that 1) the four values of Islamic education that are found in the Nengah Nyappur philosophy in Muara Jaya Village II are above them (a) mutual appreciation (b). Please help. (c) Goodbye to Mufakat and, (d) Friendly. (a) Gotong royong (b) Ketekhom jejama (c) Hipun or himpun (d) compact and please help. 3) Implications Internalization of Nengah Nyappur philosophy to internalize the character of the young religious of Lampung Saibatin in Muara Jaya Village II. a) Low heart. b) Cut royong. c) Tenggang taste and love each other. The conclusion of this study is that it responds to what is the formula of the problem in this study.